Effect of Risk Management Practices on Project Delivery in IT Infrastructure Projects in Chad - Cinar, Nicolas (International Journal of Project Management, 2024)
Purpose: The aim of the study was to assess the effect of risk management practices on project delivery in it infrastructure projects in Chad. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that effective risk management significantly contributes to project success by identifying, analyzing, and mitigating potential risks. Projects that implemented robust risk management practices experienced fewer cost overruns, schedule delays, and scope changes compared to those with poor risk management strategies. Additionally, proactive risk management led to better decision-making, improved stakeholder communication, and increased overall project performance. The findings underscore the importance of integrating risk management into project planning and execution to enhance project delivery outcomes in IT infrastructure projects. Implications to Theory, Practice and Policy: Contingency theory, agency theory and resource dependency theory may be used to anchor future studies on assessing the effect of risk management practices on project delivery in it infrastructure projects in Chad. In terms of practical implications, organizations in the IT infrastructure sector should adopt tailored risk management strategies aligned with their industry, project scope, organizational culture, and risk appetite. Policymakers should collaborate with industry stakeholders to develop regulatory frameworks and standards that promote effective risk management practices in IT infrastructure projects.